Hazards of Using Masking Protocols When Performing Ligand Binding Assays: Lessons From the Sigma-1 and Sigma-2 Receptors - Abbas, Haider; Borde, Preeti; Willars, Gary B.; Ferry, David R.; Safrany, Stephen T. (Frontiers in Pharmacology, 2020)
Sigma-1 and sigma-2 receptors are emerging therapeutic targets. Although the molecular identity of the sigma-2 receptor has recently been determined, receptor quantitation has used, and continues to use, the sigma-1 selective agents (+) pentazocine or dextrallorphan to mask the sigma-1 receptor in radioligand binding assays. Here, we have assessed the suitability of currently established saturation and competition binding isotherm assays that are used to quantify parameters of the sigma-2 receptor. We show that while the sigma-1 receptor mask (+) pentazocine has low affinity for the sigma-2 receptor (Ki 406 nM), it can effectively compete at this site with [³H] di-O-tolyl guanidine (DTG) at the concentrations frequently used to mask the sigma-1 receptor (100 nM and 1 µM). This competition influences the apparent affinity of DTG and other ligands tested in this system. A more troublesome issue is that DTG can displace (+) pentazocine from the sigma-1 receptor, rendering it partly unmasked. Indeed, commonly used concentrations of (+) pentazocine, 100 nM and 1 µM, allowed 37 and 11 % respectively of sigma-1 receptors to be bound by DTG (300 nM), which could result in an overestimation of sigma-2 receptor numbers in assays where sigma-1 receptors are also present. Similarly, modelled data for 1 µM dextrallorphan show that only 71-86 % of sigma-1 receptors would be masked in the presence of 300 nM DTG. Therefore, the use of dextrallorphan as a masking agent would also lead to the overestimation of sigma-2 receptors in systems where sigma-1 receptors are present. These data highlight the dangers of using masking agents in radioligand binding studies and we strongly recommend that currently used masking protocols are not used in the study of sigma-2 receptors. In order to overcome these problems, we recommend the use of a cell line apparently devoid of sigma-1 receptors (e.g., MCF7 (ATCC HTB-22)) in the absence of any masking agent when determining the affinity of agents for the sigma-2 receptor. In addition, assessing the relative levels of sigma-1 and sigma-2 receptors can be achieved using [³H] DTG saturation binding followed by two-site analysis of (+) pentazocine competition binding with [³H] DTG.